The Prembion® pre-biotic improves the impact of anti-CTLA4 immune checkpoint inhibitor in a murine model of malignant pleural mesothelioma. (1st June 2022) - Gattlen, C; Chriqui, L-E; Hao, Y; Gonzalez, M; Krueger, T; Siankevich, S; Dyson, P; Cavin, S; Perentes, J-Y
Abstract: Objective: Immune checkpoint inhibition (ICI) therapy has revolutionized the outcome of certain cancers such as malignant pleural mesothelioma (MPM). However, patient responsiveness to this treatment remains unpredictable. Recently, a role for the gut microbiota composition has emerged for patients to generate a robust immune response against their tumors, following immunotherapy. Here, we studied the impact of Prembion®, a pre-biotic and modulator of the gut microbiota, on tumor control and lymphocyte infiltration in a murine MPM model treated by ICI. Methods: Prembion® (diluted into drinking water) was administrated to BALBc mice for 14 days. These animals were then inoculated orthotopically with a syngeneic MPM cell line (AB12-luc cells injected in the pleura) and followed by bioluminescence imaging. We determined the tumor growth and mouse survival in different groups: untreated control, Prembion®, IgG control, anti-PDL-1, anti-CTLA4, Prembion®+anti-PDL-1 and Prembion®+anti-CTLA4. A correlation between tumor response/animal survival and MPM infiltration with CD8+ lymphocytes was also performed by immunohistochemistry. Results: Prembion® was well tolerated and did not affect animal weight or activity. Interestingly, Prembion® was as effective as anti-PDL1 and anti-CTLA4 monotherapy on tumor control, prolonging survival by 4.0 ± 1.1 days compared to controls (p<0.05). Moreover Prembion® potentiated anti-CTLA4 efficacy with a significant improvement in mouse survival of the Prembion®+anti-CTLA4 compared to controls (3.6 ± 1.1 days, p<0.05). Additionally, this finding correlated with enhanced MPM infiltration by CD8+ lymphocytes compared to controls (p<0.05). Conclusion: Prembion® positively regulated the adaptive immune response against MPM and helped to improve the impact of anti-CTLA4 ICI on MPM. Further work focusing on the gut microbiome changes induced by Prembion® are ongoing to better understand the mechanisms involved.